Theta-Burst Stimulation over the pre-Supplementary Motor Area in Schizophrenia and comorbid substance use disorder: Preliminary clinical data - Stefano Pallanti; Michele Di Ponzio; Nikos Makris; Marek Kubicki (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Schizophrenia (SZ) is a debilitating disorder, which tremendously impacts the psychological, social, and financial aspects of a patient's life. Frequently, SZ patients present with poor insight, which can even worsen the symptomatology. Antipsychotic medications frequently result in suboptimal outcomes, especially the ones concerning negative and cognitive symptoms. Accordingly, new therapeutic options are warranted. Transcranial Magnetic Stimulation (TMS) has been adopted in SZ with promising results. Continuous Theta burst stimulation (cTBS) is a particular brief and effective form of TMS. It has been successfully applied in patients with poor cognitive control (e.g., gambling disorder patients) targeting the pre-Supplementary Motor Area (pre-SMA). Given that poor cognitive control has been regarded as a core deficit in SZ, 11 patients with SZ were included in this study and treated with cTBS for a total of 10 sessions during a two-week period. Patients were divided into two groups: patients with a diagnosis of SZ in comorbidity with Substance Use Disorder (SZ + SUD) vs SZ. Patients were evaluated before and after treatment, assessing executive functions, awareness, and nicotine craving. Within-group comparisons showed a significant reduction in the Scale to assess Unawareness in Mental Disorders (SUMD) scores (p < 0.05) and in the test of Fagerstrom (to assess nicotine dependence) scores (p < 0.001) before and after treatment in the SZ + SUD group. These results showed the efficacy of cTBS for craving reduction as well as in improving awareness of the illness and of treatment. This can be considered a remarkable result since better insight has been previously associated with an improved quality of life in SZ.